ANALISIS PRODUKSI USAHATANI PADI SAWAH DI DESA PENYESAWAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Hamdan Yasid; Asgami Putri; Khairunnas Khairunnas (Indonesian Journal of Agricultural Economics, 2022)
Increasing national rice production continues to be carried out in the context of meeting the people's food needs and as an effort to strengthen national food security. This was done considering that Indonesia's population reached 258.7 million people in 2016, with a growth rate of 1.36% year. In addition, the level of rice consumption is still quite high, reaching 114.6 kg/capita/year, so it requires a large enough food supply by increasing the production of food commodities, especially rice. Rice is still the main staple food source for the people.Sampling in the Production Analysis of Lowland Rice Farming in Penyesawan Village, Kampar District was carried out using the Taro Yamane formula where if the population exceeds 100, the precision used is 15% - 20%. The sample used was 38 respondents.Data analysis was carried out using appropriate formulas to answer the stated research objectives. The results of data analysis of lowland rice production in Penyesawan Village, Kampar District, Kampar Regency is an average of 607 kg with an income of 6,071,316/MT. While the net income of paddy farmers in one planting season is IDR 3,888,942. With an average value of R/C Ratio obtained for rice farming in Penyesawan Village, Kampar District, Kampar Regency of 2.9, thus the profit eligibility system applied is feasible to be developed in Penyesawan Village, Kampar District, Kampar Regency, because every Rp. 100, - issued in at the beginning of lowland rice farming activities, revenue of IDR 290 was obtained